Marketing Policy And Competitiveness In The Manufacturing Sector In Uganda: A Case of Uganda Clays Ltd - Rukanyangira, Nazarious; Mande Muyinda, Wilson; Mawa, Michael (Researchjournali’s Journal of Marketing, 2018)
The current study set out to analyse the effect of Marketing Policy on Competitiveness in the manufacturing sector with specific reference to Uganda Clays Ltd. In order to achieve the above purpose the study objective was; To measure the contribution of Marketing Policy to Competitiveness in the manufacturing sector in Uganda. The current study applied the post-positivist paradigm and employed a descriptive cross-sectional survey design. The main Approach used was Quantitative but Qualitative method and/or approach was also employed on limited Scale. The findings revealed that Marketing Policy had a strong positive significant relationship with Competitiveness (r=(160).547, P<0.01), which meant marketing Policy has an impact on Competitiveness. However the Competitiveness referred to only applied to the current environment which did not promise continued Survival into the future. Given that fact the study has proposed the SUPMAP
Keywords: Marketing Policy; Competitiveness; SUPMAP Model